Green bio-based fiber module soil and preparation method thereof

By adding a specific proportion of bio-based materials and fiber sustained-release particles to the fiber module soil, the problem of insufficient water retention and sustained-release performance of fiber module soil in the prior art is solved, and the effect of long-term soil improvement and plant growth support is achieved, while also having environmentally friendly degradation properties.

CN119552022APending Publication Date: 2025-03-04ZHONGAO ECOLOGICAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411741837.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing fiber module soil has limitations in water retention properties and the sustained release properties of nutrients, making it difficult to meet the needs of long-term soil improvement and plant growth support.

Method used

A green bio-based fiber modular soil is used, which includes a specific proportion of peat soil, garden waste, distillery lees, crop straw, humus, minerals and fiber sustained release particles. The fiber sustained-release particles are prepared by wrapping the fiber membrane and hydrogel particles to form a urea carrier with good storage and sustained-release properties.

Benefits of technology

It significantly improves the water retention performance of fiber module soil and the sustained release performance of nutrients, realizes long-term improvement of soil and continuous support for plant growth, and is environmentally friendly and easy to degrade.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162764490000131
    Figure BDA0005162764490000131
Patent Text Reader

Abstract

The invention relates to the technical field of fiber module soil, and provides green bio-based fiber module soil which comprises peat soil, garden waste, vinasse, crop straw, humus, mineral substances and fiber slow-release particles. Wherein the fiber sustained-release particles are composed of hydrogel particles internally loaded with urea and fiber membranes coating the hydrogel particles, the hydrogel particles can play a good storage effect on the urea due to pore structures of the hydrogel particles and prevent the urea from being rapidly released, and the external fiber membranes further prevent the urea from being released; hA of the fiber membrane contains a large number of hydroxyl groups and hydroxyl functional groups, so that the hydrophilicity of a membrane layer can be improved, meanwhile, carrier hydrogel particles in internal nutrient particles have relatively high specific surface area and porosity due to a self-pore effect, so that the whole fiber sustained-release particles have good moisture absorption performance and water retention performance, and the fiber sustained-release effect is improved. The growth of microorganisms is facilitated, and the biodegradation of the film layer is further facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fiber module soil, and in particular to a green bio-based fiber module soil and a preparation method thereof. Background Art

[0002] In modern environmental governance, fiber modular soil, as an innovative soil improvement material, has gradually attracted widespread attention. Traditional soil improvement methods, such as adding chemical modifiers or physical reinforcement, have improved the mechanical properties and stability of the soil to a certain extent, but often cause environmental pollution. In order to solve these problems, green bio-based fiber modular soil came into being.

[0003] Green bio-based fiber modular soil is a soil improvement material made from renewable and degradable biomaterials through a specific process. Its core advantage is that it can significantly improve the water retention and slow-release properties of the soil, thereby achieving long-term soil improvement and continuous support for plant growth. It is also easy to degrade and more environmentally friendly. However, the existing fiber modular soil is still subject to many limitations in terms of water retention and slow-release properties of nutrients, which has become a technical problem that needs to be solved urgently. Summary of the invention

[0004] The present invention provides a green bio-based fiber module soil and a preparation method thereof, which solves the problem of how to improve the water retention performance and the slow-release performance of the nutrient components of the fiber module soil in the related art.

[0005] The technical solution of the present invention is as follows:

[0006] In the first aspect, the present invention proposes a green bio-based fiber modular soil, comprising the following raw materials in parts by weight: 170-190 parts of peat soil, 20-30 parts of garden waste, 10-20 parts of distiller's grains, 50-70 parts of crop straw, 20-30 parts of humus, 30-40 parts of minerals, and 40-50 parts of fiber slow-release particles; in the present invention, the following raw materials in parts by weight are preferred: 180 parts of peat soil, 25 parts of garden waste, 15 parts of distiller's grains, 60 parts of crop straw, 25 parts of humus, 35 parts of minerals, and 45 parts of fiber slow-release particles.

[0007] Preferably, the garden waste is waste leaves of plants trimmed during garden maintenance, including waste leaves of trees and / or waste leaves of flowers and plants.

[0008] Preferably, the crop straw includes a combination of any one or more of corn straw, wheat straw, soybean straw, rice straw and peanut straw; in the present invention, the crop is more preferably a mixture of corn straw, wheat straw and soybean straw in a mass ratio of 1:1:1.

[0009] Preferably, the mineral includes any one or more of lime, limestone, phosphogypsum, desulfurized gypsum, and bentonite; in the present invention, the mineral is more preferably a mixture of limestone, desulfurized gypsum, and bentonite in a mass ratio of 1:2:3.

[0010] Furthermore, the fiber slow-release particles are prepared by the following method:

[0011] The nutrient particles were placed in a drum coater and preheated at 70°C for 10 min. The fiber membrane liquid was then repeatedly and evenly sprayed on the surface of the nutrient particles at a fan temperature of 80°C, a drum coater speed of 40 r / min, and a coating time of 20 min to form a fiber membrane. The spraying amount of the fiber membrane liquid could be freely adjusted by the spraying rate. Finally, the particles were placed in a vacuum drying oven and heated at 80°C for 30 min to obtain fiber sustained-release particles.

[0012] Preferably, the ratio of the amount of the nutrient particles to the amount of the fiber membrane liquid sprayed is 1 g: (0.2-0.4) mL; in the present invention, the ratio of the amount of the nutrient particles to the amount of the fiber membrane liquid sprayed is more preferably 1 g: 0.3 mL.

[0013] Furthermore, the nutritional granules are prepared according to the following steps:

[0014] Step A1, dissolving sodium carboxymethyl cellulose (CMC) in dimethylformamide (DMF) and stirring evenly to obtain a CMC solution; dissolving diatomaceous earth (DE) in nitric acid (HNO) with a mass fraction of 12%-18%; 3 ) solution for 2 hours, then centrifuged, washed the precipitate obtained by centrifugation with clean water until the pH reached 7, then transferred to a vacuum drying oven and dried at 80°C for 4 hours to obtain nitrated diatomaceous earth (NDE), added NDE to the CMC solution, and added a crosslinking agent dropwise, then reacted at 80°C for 6 hours under nitrogen protection, and the obtained product was repeatedly washed with clean water to remove DMF, and finally a milky white sticky hydrogel precursor was obtained;

[0015] Step A2: Add 0.1 mol / L ferric chloride (FeCl) to the hydrogel precursor using a syringe. 3 ) solution to form a hydrogel, which is then filtered using a funnel, the filter material is repeatedly washed with pure water, and then placed in a vacuum drying oven to dry at 60° C. for 5 h, taken out and ground in a grinder to obtain hydrogel particles with a particle size of 2-4 mm;

[0016] Step A3, dissolving urea in water to form a urea solution, the mass ratio of urea to water is 3g:10mL, then soaking the hydrogel particles in the urea solution for 24 hours, and then filtering, the obtained filter material is transferred to a vacuum drying oven and dried at 60°C for 4 hours to obtain nutrient particles.

[0017] Preferably, in step A1, the usage ratio of CMC to DMF is 1 g:50 mL.

[0018] Preferably, in step A1, the usage ratio of CMC to DE is 1:1.

[0019] Preferably, in step A1, the volume ratio of the cross-linking agent to DMF is 1:100.

[0020] Preferably, in step A1, the crosslinking agent is any one of vinyl trimethoxy silane (VTMS), dimethylol dihydroxy ethylene urea (DLDL), and hexamethylene diisocyanate (HDI), more preferably VTMS.

[0021] When preparing nutrient granules, DE is nitrated to obtain NDE, which can increase its associated hydroxyl groups and make CMC more stably grafted to NDE under the action of crosslinking agent to generate hydrogel precursor. 3 After the solution is further cross-linked, the surface roughness and looseness of the hydrogel precursor can be further increased, resulting in agglomeration, thereby exposing more active sites to promote the adsorption of urea solution and increase the urea loading capacity; at the same time, the storage mechanism of the pore structure on the hydrogel surface can also intercept urea to prevent urea from being released quickly, thus achieving good sustained-release performance.

[0022] Furthermore, the fiber membrane liquid is prepared according to the following steps:

[0023] Step B1, dissolving polylactic acid (PLA) in deionized water to obtain a PLA solution, dissolving hyaluronic acid (HA) in deionized water to obtain a HA solution, mixing the PLA solution and the HA solution, stirring at 50° C. for 1 h, then adding acetic acid dropwise to adjust the pH to 3.5, then adding glutaraldehyde and stirring at 50° C. for 1 h to obtain a mixed solution;

[0024] Step B2: Add magnesium chloride (MgCl) to the mixed solution. 2 ) and stirred evenly to obtain fiber membrane liquid.

[0025] Preferably, in step B1, the mass fraction of PLA in the PLA solution is 10%.

[0026] Preferably, in step B1, the mass fraction of HA in the HA solution is 10%.

[0027] Preferably, in step B1, the usage ratio of PLA to HA is 4:1.

[0028] Preferably, in step B1, the ratio of the total volume of the PLA solution and the HA solution to the amount of glutaraldehyde is 100:1.

[0029] Preferably, in step B2, the usage ratio of MgCl2 to PLA is 1:10.

[0030] When preparing the fiber membrane solution, PLA and HA undergo cross-linking reaction under the action of cross-linking agent glutaraldehyde, so that PLA molecules penetrate and entangle with each other to form acetal rings, resulting in the destruction of the molecular arrangement order, thereby reducing its crystallinity. At the same time, cross-linking can act as a defect center to hinder the folding of the macromolecular chain, thereby further reducing the crystallinity. After the cross-linking reaction, the glucuronic acid in HA binds to MgCl 2 Mg 2+ Through ionic bond connection, a three-dimensional network structure is formed, making the film structure more compact and stable after film formation. Therefore, after coating the nutrient particles, it can prevent the rapid release of nutrients, which is beneficial to improve the sustained release of nutrients.

[0031] At the same time, HA contains a large number of hydroxyl groups and hydroxyl functional groups, which can improve the hydrophilicity of the membrane layer, making it have good hygroscopic properties, which is conducive to the growth of microorganisms and further conducive to the biodegradation of the membrane layer.

[0032] In a second aspect, the present invention further discloses a method for preparing the green bio-based fiber modular soil as described above, comprising the following steps:

[0033] S1, crushing crop straw to obtain powder, heating the powder at 120° C. for 3 h to obtain a soft material;

[0034] S2. Mix the soft material with peat soil, humus, minerals and fiber slow-release particles and stir evenly, then fill them into the module template, let them stand for 12 hours and then demould to obtain fiber module soil.

[0035] The working principle and beneficial effects of the present invention are:

[0036] 1. The green bio-based fiber module soil of the present invention is added with fiber slow-release particles, the fiber slow-release particles are wrapped with fiber membranes on the outside, and the inside is composed of hydrogel particles adsorbing nutrient urea. The hydrogel particles can have a good storage effect on urea due to their pore structure, prevent urea from being released quickly, enhance its slow-release performance, and play the role of the first barrier layer for slow-release urea. In addition, after passing through the first barrier layer, urea also needs to pass through the fiber membrane as the second barrier layer. During the formation of this fiber membrane layer, PLA and HA undergo a cross-linking reaction under the action of a cross-linking agent, glutaraldehyde, so that PLA molecules penetrate and entangle with each other to form acetal rings, resulting in the destruction of the molecular arrangement order, thereby reducing its crystallinity. At the same time, cross-linking can serve as a defect center to hinder the folding of the macromolecular chain, thereby further reducing the crystallinity. After the cross-linking reaction, the glucuronic acid in HA and MgCl 2 Mg 2+ Through ionic bond connection, a three-dimensional network structure is formed, making the thick film layer structure more compact and stable. Therefore, after coating the nutrient particles, it can prevent the rapid release of nutrients, thereby further enhancing its sustained-release performance.

[0037] 2. In the green bio-based fiber module soil of the present invention, the fiber membrane outside the slow-release particles contains HA, and HA contains a large number of hydroxyl groups and hydroxyl functional groups, so the hydrophilicity of the membrane layer can be improved. At the same time, the carrier hydrogel particles in the internal nutrient particles have a higher specific surface area and porosity due to their own pore effect, so that the fiber slow-release particles as a whole have good moisture absorption and water retention properties, which is beneficial to the growth of microorganisms and further beneficial to the biodegradation of the membrane layer. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The experimental methods in the following preparation examples and embodiments are conventional methods unless otherwise specified, and are carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following embodiments are all commercially available unless otherwise specified.

[0040] Preparation Example 1

[0041] Preparation of nutritional granules:

[0042] Step 1: Dissolve 10 g of CMC in a beaker containing 500 mL of DMF and stir evenly to obtain a CMC solution; dissolve 10 g of DE in a beaker containing 100 mL of 15% HNO 3 The solution was stirred in a beaker for 2 hours, then transferred to a centrifuge for centrifugal separation, the precipitate obtained by centrifugation was washed with clean water until the pH reached 7, and then transferred to a vacuum drying oven for drying at 80°C for 4 hours to obtain NDE, NDE was added to the CMC solution, and 5 mL of VTMS was added dropwise, and then transferred to a stirring tank for stirring and reacting at 80°C for 6 hours under nitrogen protection, the obtained product was repeatedly washed with clean water to remove DMF, and finally a milky white sticky hydrogel precursor was obtained;

[0043] Step 2: using a syringe to dropwise add the hydrogel precursor into a FeCl3 solution with a concentration of 0.1 mol / L to form a hydrogel, and then filtering using a funnel, repeatedly washing the filter material with pure water, and then transferring it to a vacuum drying oven and drying it at 60°C for 5 hours, taking it out and grinding it in a grinder to obtain hydrogel particles with a particle size of 2-4 mm;

[0044] Step 3: Dissolve 60 g of urea in 200 mL of water and stir evenly to form a urea solution with a mass fraction of 0.3 g / mL. Then, soak the hydrogel particles in the urea solution for 24 hours, filter it, and transfer the filter material to a vacuum drying oven and dry it at 60°C for 4 hours to obtain nutrient particles.

[0045] Comparative Preparation Example 1

[0046] Preparation of nutritional granules:

[0047] Step 1: Dissolve 10 g of CMC in a beaker containing 500 mL of DMF and stir evenly to obtain a CMC solution; add 10 g of DE to the CMC solution, and drop 5 mL of VTMS, then transfer to a stirring tank and stir at 80 ° C for 6 hours under nitrogen protection. The obtained product is repeatedly washed with clean water to remove DMF, and finally a milky white viscous hydrogel precursor is obtained;

[0048] Step 2: using a syringe to dropwise add the hydrogel precursor into a FeCl3 solution with a concentration of 0.1 mol / L to form a hydrogel, and then filtering using a funnel, repeatedly washing the filter material with pure water, and then transferring it to a vacuum drying oven and drying it at 60°C for 5 hours, taking it out and grinding it in a grinder to obtain hydrogel particles with a particle size of 2-4 mm;

[0049] Step 3: Dissolve 60 g of urea in 200 mL of water and stir evenly to form a urea solution with a mass fraction of 0.3 g / mL. Then, soak the hydrogel particles in the urea solution for 24 hours, filter it, and transfer the filter material to a vacuum drying oven and dry it at 60°C for 4 hours to obtain nutrient particles.

[0050] Comparative Preparation Example 2

[0051] Preparation of nutritional granules:

[0052] Step 1: Dissolve 10 g of CMC in a beaker containing 500 mL of DMF and stir evenly to obtain a CMC solution; dissolve 10 g of DE in a beaker containing 100 mL of 15% HNO 3 The solution was stirred in a beaker for 2 hours, then transferred to a centrifuge for centrifugal separation, the precipitate obtained by centrifugation was washed with clean water until the pH reached 7, and then transferred to a vacuum drying oven for drying at 80°C for 4 hours to obtain NDE, NDE was added to the CMC solution, and 5 mL of VTMS was added dropwise, and then transferred to a stirring tank for stirring and reacting at 80°C for 6 hours under nitrogen protection, the obtained product was repeatedly washed with clean water to remove DMF, and finally a milky white sticky hydrogel precursor was obtained;

[0053] Step 2: Place the hydrogel precursor in a vacuum drying oven at 60° C. and dry for 5 h. Take it out and grind it in a grinder to obtain hydrogel particles with a particle size of 2-4 mm.

[0054] Step 3: Dissolve 60 g of urea in 200 mL of water and stir evenly to form a urea solution with a mass fraction of 0.3 g / mL. Then, soak the hydrogel particles in the urea solution for 24 hours, filter it, and transfer the filter material to a vacuum drying oven and dry it at 60°C for 4 hours to obtain nutrient particles.

[0055] The performance tests were performed on the nutrient granules prepared in Preparation Example 1 and Comparative Preparation Examples 1-2, respectively. The test method was as follows: 5 g of nutrient granules were placed in 100 mL of deionized water, stirred continuously at 200 rpm, and the supernatant was taken every 1 h to measure the urea content using a residual chlorine detector until the urea content did not change. The final value at which the urea content no longer changed and the time at which the final value was reached were recorded, and the recorded results were listed in Table 1. Table 1 is as follows:

[0056] Table 1

[0057] Final value of urea content (g / mL) Time to reach final value (h) Preparation Example 1 0.0225 21 Comparative Preparation Example 1 0.0125 11 Comparative Preparation Example 2 0.0101 9

[0058] By analyzing the data in Table 1, it can be seen that, compared with Comparative Preparation Examples 1-2, the nutrient granules prepared in Preparation Example 1 can adsorb more urea and release urea more slowly, so they have stronger storage performance and sustained release performance for urea.

[0059] Preparation Example 2

[0060] Preparation of fiber membrane solution:

[0061] Step 1: dissolve 100 g of PLA in 900 g of deionized water and stir to obtain a PLA solution; dissolve 25 g of HA in 225 g of deionized water and stir to obtain a HA solution; mix the PLA solution and the HA solution, stir at 50° C. for 1 h, then add acetic acid dropwise to adjust the pH to 3.5, then add 11.25 g of glutaraldehyde and stir at 50° C. for 1 h to obtain a mixed solution;

[0062] Step 2: Add 10 g of MgCl to the mixture. 2 Stir evenly to obtain fiber membrane liquid.

[0063] Comparative Preparation Example 3

[0064] Preparation of fiber membrane solution:

[0065] Step 1: dissolve 100 g of PLA in 900 g of deionized water and stir evenly to obtain a PLA solution;

[0066] Step 2: Add 10 g of MgCl to the PLA solution. 2 Stir evenly to obtain fiber membrane liquid.

[0067] Comparative Preparation Example 4

[0068] Preparation of fiber membrane solution:

[0069] 100 g of PLA was dissolved in 900 g of deionized water and stirred to obtain a PLA solution; 25 g of HA was dissolved in 225 g of deionized water and stirred to obtain a HA solution; the PLA solution and the HA solution were mixed, stirred at 50°C for 1 hour, and then acetic acid was added dropwise to adjust the pH to 3.5, and then 11.25 g of glutaraldehyde was added and stirred at 50°C for 1 hour to obtain a fiber membrane solution.

[0070] Preparation Example 3

[0071] Preparation of fiber sustained-release granules: 18 g of the nutritional granules prepared in Preparation Example 1 were placed in a drum coater, preheated at 70°C for 10 min, and then the fiber membrane liquid prepared in Preparation Example 2 was repeatedly and evenly sprayed on the surface of the nutritional granules at a spraying rate of 0.27 g / min with a fan temperature of 80°C, a drum coater speed of 40 r / min, and a coating time of 20 min to form a fiber membrane; finally, the fiber was transferred to a vacuum drying oven and heated at 80°C for 30 min to obtain the fiber sustained-release granules.

[0072] Comparative Preparation Example 5

[0073] Preparation of fiber sustained-release particles: Compared with Preparation Example 3, the only difference is that the nutritional particles prepared in Preparation Example 1 are replaced by the nutritional particles prepared in Comparative Preparation Example 1, and other conditions remain the same, and finally fiber sustained-release particles are prepared.

[0074] Comparative Preparation Example 6

[0075] Preparation of fiber sustained-release particles: Compared with Preparation Example 3, the only difference is that the nutritional particles prepared in Preparation Example 1 are replaced by the nutritional particles prepared in Comparative Preparation Example 2, and other conditions remain the same, and finally fiber sustained-release particles are prepared.

[0076] Comparative Preparation Example 7

[0077] Preparation of fiber sustained-release particles: Compared with Preparation Example 3, the only difference is that the fiber membrane liquid prepared in Preparation Example 2 is replaced by the fiber membrane liquid prepared in Comparative Preparation Example 3, and other conditions remain the same, and finally fiber sustained-release particles are prepared.

[0078] Comparative Preparation Example 8

[0079] Preparation of fiber sustained-release particles: Compared with Preparation Example 3, the only difference is that the fiber membrane liquid prepared in Preparation Example 2 is replaced by the fiber membrane liquid prepared in Comparative Preparation Example 4, and other conditions remain the same, and finally fiber sustained-release particles are prepared.

[0080] The fiber sustained-release particles obtained from Preparation Example 3 and Comparative Preparations 5-8 were subjected to performance tests, including water absorption test, contact angle test, and compressive strength test. The test methods are as follows.

[0081] Water absorption test: Take 5g of fiber sustained-release particle sample and place it in an oven, dry it at 70℃ for 2h, and get a constant mass W1 after taking it out; then soak the sample in distilled water for 24h, take it out and remove the surface moisture with filter paper, weigh its mass and record it as W2, calculate the water absorption based on W1 and W2, water absorption = [(W2-W1) / W1]×100%, test each group of samples three times and take the average value.

[0082] Contact angle test: The contact angle of the obtained film was measured using a contact angle tester (GR001 PC130D, China Jinzhitang). 1uL of water was dropped on the surface of the fiber sustained-release particle sample, and the image was collected using a digital optical microscope. The contact angle was calculated using a dedicated analysis software. Each group of samples was tested three times and the average value was taken.

[0083] Compressive strength test: Use a particle strength tester to measure the compressive strength of the fiber slow-release particle sample. Place the test sample in the center of the sample plate, rotate the upper handwheel clockwise, move the force rod downward, and the data on the display increases with the increase of the test force. When the sample particles are broken, the maximum force value is locked, and the digital display directly displays the maximum strength value. Each group of samples is tested three times and the average value is taken.

[0084] The above test results are listed in Table 2, which is as follows:

[0085] Table 2

[0086] Water absorption (100%) Contact angle (°) Compressive strength(N) Preparation Example 3 562.3 35.6 32 Comparative Preparation Example 5 398.5 36.2 15 Comparative Preparation Example 6 405.2 26.4 12 Comparative Preparation Example 7 256.3 77.9 14 Comparative Preparation Example 8 325.1 56.2 16

[0087] By analyzing the data in Table 2, it can be seen that compared with comparative preparation examples 5-8, the fiber sustained-release particles prepared in preparation example 3 have a higher water absorption rate and a smaller contact angle, which indicates that it has stronger hygroscopic properties. At the same time, the compressive strength is significantly higher, indicating that it has excellent mechanical properties.

[0088] Example 1

[0089] Preparation of green bio-based fiber module soil:

[0090] Step 1: Mix 2g corn straw, 2g wheat straw, 2g soybean straw, and 2.5g waste leaves of flowers and plants pruned from the garden, and then crush them to obtain a powder, and heat the powder at 120° C. for 3h to obtain a soft material;

[0091] Step 2: Mix the soft material with 1.5g of wine lees, 18g of peat soil, 2.5g of humus, 3.5g of bentonite, and 4.5g of the fiber slow-release particles prepared in Preparation Example 3 for 2h, then fill it into a square glass template with a size of 4cm*4cm, let it stand for 12h, and then demold it to obtain fiber module soil.

[0092] Example 2

[0093] Step 1: Mix 2g corn straw, 1.5g wheat straw, 1.5g waste leaves of flowers and plants pruned from the garden, and 2g soybean straw, and crush them to obtain a powder, and heat the powder at 120° C. for 3h to obtain a soft material;

[0094] Step 2: Mix the soft material with 1g of wine lees, 17g of peat soil, 2g of humus, 3g of bentonite, and 4g of the fiber slow-release particles prepared in Preparation Example 3 for 2h, then fill it into a square glass template with a size of 4cm*4cm, let it stand for 12h, and then demold it to obtain fiber module soil.

[0095] Example 3

[0096] Step 1: 2 g corn straw, 2.5 g wheat straw, 2.5 g soybean straw, and 3 g of waste leaves of gardening plants were mixed and crushed to obtain a powder, and the powder was heated at 120° C. for 3 h to obtain a soft material;

[0097] Step 2: Mix the soft material with 2g of wine lees, 19g of peat soil, 3g of humus, 4g of bentonite, and 5g of the fiber slow-release particles prepared in Preparation Example 3 for 2h, then fill it into a square glass template with a size of 4cm*4cm, let it stand for 12h, and then demold it to obtain fiber module soil.

[0098] Comparative Example 1

[0099] Compared with Example 1, the only difference is that the fiber slow-release particles prepared in Preparation Example 3 are replaced by the fiber slow-release particles prepared in Comparative Preparation Example 5, and other conditions remain the same, and finally fiber modular soil is obtained.

[0100] Comparative Example 2

[0101] Compared with Example 1, the only difference is that the fiber slow-release particles prepared in Preparation Example 3 are replaced by the fiber slow-release particles prepared in Comparative Preparation Example 6, and other conditions remain the same, and finally fiber modular soil is obtained.

[0102] Comparative Example 3

[0103] Compared with Example 1, the only difference is that the fiber slow-release particles prepared in Preparation Example 3 are replaced by the fiber slow-release particles prepared in Comparative Preparation Example 7, and other conditions remain the same, and finally fiber modular soil is obtained.

[0104] Comparative Example 4

[0105] Compared with Example 1, the only difference is that the fiber slow-release particles prepared in Preparation Example 3 are replaced by the fiber slow-release particles prepared in Comparative Preparation Example 8, and other conditions remain the same, and finally fiber modular soil is obtained.

[0106] The fiber module soil prepared by the preparation method of Examples 1-3 and Comparative Examples 1-4 was subjected to a performance test to test the water retention performance and the sustained release performance of nutrients (urea) of the fiber module soil. The method is as follows.

[0107] Water retention rate: Add 100 g of fiber module soil sample into a beaker, add 50 mL of water into the beaker and weigh its weight, weigh and record it every 3 days for 30 days, and calculate its water retention rate. Water retention rate (W30) = [(M30-M0) / (M1-M0)] × 100%, where M0 is the total mass of the fiber module soil sample and beaker, M1 is the total mass of the fiber module soil sample, beaker and water, and M30 is the total mass of the fiber module soil sample, beaker and remaining water after 30 days.

[0108] Sustained release performance: 100 g of fiber module soil was added into a chromatography column (22 mm × 500 mm) with a sand core, 50 mL of water was added into the chromatography column, 5 mL of leachate was collected every three days, and 5 mL of water was added into the chromatography column to keep the moisture constant. The absorbance of urea in the soil leachate was determined at 880 nm using a UV-visible spectrophotometer, and the cumulative release rate of urea was calculated.

[0109] The test results of water retention rate and sustained release performance are listed in Table 3. Table 3 is as follows:

[0110] Table 3

[0111]

[0112] By analyzing the data in Table 3, it can be seen that compared with Comparative Examples 1-4, the fiber module soil prepared in Examples 1-3 has stronger water retention performance and a slow release effect on nutrients (urea).

[0113] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A green bio-based fiber module soil, characterized in that: The raw materials include the following parts by weight: 170-190 parts of peat soil, 20-30 parts of garden waste, 10-20 parts of distiller's grains, 50-70 parts of crop straw, 20-30 parts of humus, 30-40 parts of minerals, and 40-50 parts of fiber slow-release particles; Wherein, the fiber slow-release particles are prepared by the following method: The nutrient particles were placed in a drum coater, preheated at 70°C for 10 min, and then the fiber membrane liquid was repeatedly and evenly sprayed on the surface of the nutrient particles at a fan temperature of 80°C, a drum coater speed of 40 r / min, and a coating time of 20 min to form a fiber membrane; finally, the fiber was heated at 80°C for 30 min to obtain fiber slow-release particles.

2. The green bio-based fiber module soil according to claim 1, characterized in that: The ratio of the amount of the nutrient particles to the amount of the fiber membrane liquid sprayed is 1g: (0.2-0.4)mL.

3. The green bio-based fiber module soil according to claim 1, characterized in that: The nutritional granules are prepared according to the following steps: Step A1, dissolving sodium hydroxymethyl cellulose in dimethylformamide and stirring evenly to obtain a CMC solution; then nitrifying diatomaceous earth, adding it to the CMC solution, and dropping a crosslinking agent, and then reacting at 80° C. for 6 hours under nitrogen protection, and washing to obtain a hydrogel precursor; Step A2, adding the hydrogel precursor dropwise into a 0.1 mol / L ferric chloride solution to form a hydrogel, and then filtering, washing, drying, and grinding to obtain hydrogel particles; Step A3, dissolving urea in water to form a urea solution, the mass ratio of urea to water being 3g:10mL, then soaking the hydrogel particles in the urea solution for 24 hours, and then filtering and drying to obtain nutrient particles.

4. The green bio-based fiber module soil according to claim 3, characterized in that: In step A1, the method for nitrating diatomite is: dissolving the diatomite in a nitric acid solution with a mass fraction of 12%-18% and stirring for 2 hours, then centrifuging, washing until the pH reaches 7, and then vacuum drying to obtain nitrated diatomite.

5. The green bio-based fiber module soil according to claim 3, characterized in that: In step A1, the dosage ratio of the hydroxymethyl cellulose to dimethylformamide is 1 g:50 mL, the dosage ratio of the hydroxymethyl cellulose to diatomaceous earth is 1:1, and the volume dosage ratio of the cross-linking agent to dimethylformamide is 1:

100.

6. The green bio-based fiber module soil according to claim 3, characterized in that: In step A1, the crosslinking agent is any one of vinyl trimethoxy silane, dimethylol dihydroxy ethylene urea, and hexamethylene diisocyanate.

7. The green bio-based fiber module soil according to claim 1, characterized in that: The fiber membrane solution is prepared according to the following steps: Step B1, dissolving polylactic acid in deionized water to obtain a PLA solution, dissolving hyaluronic acid in deionized water to obtain a HA solution, mixing the PLA solution and the HA solution, stirring at 50° C. for 1 h, then dropping acetic acid to adjust the pH to 3.5, then adding glutaraldehyde and stirring at 50° C. for 1 h to obtain a mixed solution; Step B2: adding magnesium chloride to the mixed solution and stirring evenly to obtain a fiber membrane solution.

8. The green bio-based fiber module soil according to claim 7, characterized in that: In step B1, the mass fraction of polylactic acid in the PLA solution is 10%, the mass fraction of hyaluronic acid in the HA solution is 10%, and the dosage ratio of polylactic acid to hyaluronic acid is 4:1; the dosage ratio of the total volume of the PLA solution and the HA solution to glutaraldehyde is 100:

1.

9. The green bio-based fiber module soil according to claim 7, characterized in that: In step B2, the ratio of magnesium chloride to polylactic acid is 1:

10.

10. A method for preparing green bio-based fiber modular soil according to any one of claims 1 to 9, characterized in that: The steps include: S1, crushing crop straw to obtain powder, heating the powder at 120° C. for 3 h to obtain a soft material; S2. Mix the soft material with peat soil, humus, minerals and fiber slow-release particles and stir evenly, then fill them into the module template, let them stand for 12 hours and then demould to obtain fiber module soil.